Accidental Spreading of 90Sr from the Ob and Yenisey Rivers under Global Warming - Gao, Yongqi; Drange, Helge; Johannessen, Ola M.; Petersson, Lasse H. (Zenodo, 2003)
The spatial and temporal distributions of the anthropogenic radionuclides 137 Cs and 90 Sr, originating from nuclear bomb testing, the Sellafield reprocessing plants in the Irish Sea, and the Ob and Yenisey river discharges, have been simulated using the Nansen Center global version of the Miami Isopycnic Co ordinate Ocean Model (MICOM). The physical model is forced with daily atmospheric re-analyses fields for the period 1950 to present. Comparison of the temp oral evolution of the observed and the simulated concentrations of 137 Cs have been conducted for the regions east of Scotland, west of central Norway, and at the entrance of the Barents Sea. Comparison of the temp oral evolution of the observed and the simulated concentrations of 90 Sr have also been performed in the Kara Sea. It is shown that the radionuclides from the Sellafield discharge reach the Barents Sea region after 4-5 years, in accordance with observations. The simulation provides a detailed distribution and evolution of the radionuclides over the integration time. For the Atlantic waters on the coast of Norway and in the southern Barents Sea, the atmospheric fallout dominates over the Sellafield release up to the mid 1960s and from the early 1990s, whereas Sella eld is the main source for the two radionuclides in the 1970s and 1980s. The Ob river discharge dominate the surface 90 Sr over most of the Arctic Ocean and along the eastern and western coasts of Greenland before 1960. During the period of 1980 to 1990, the atmospheric fallout and the Ob river discharge are equally important for the 90 Sr distribution in the Arctic Ocean. The difference between present-day and the 2xCO 2 warming scenario runs for accidental releases of 90 Sr in the Ob and Yenisey rivers indicates that the transport of the tracers can be accelerated in the 2xCO 2 warming scenario run. It also follows that more of the released 90 Sr is connected to the Arctic Ocean in the global warming run, particularly in the near coastal, non-European part of the Arctic Ocean. ...